Updated stakeholder map for Ethiopia - Mengesha, Belay Terefe (2022)
The stakeholder identification is initiated under the SHiFT initiative to identify with whom the project needs to engage with in order to achieve food system transformations. It brings together all the stakeholders working on food systems issues in a so-called ‘living’ database that can be used to quickly identify potential stakeholders. For the 2022 baseline stakeholder identification, in Ethiopia data was collected building on: existing participant lists from previous consultations under A4NH, stakeholders known from Ethiopia Food System Synthesis Report, stakeholders known from Ethiopia Food Systems Profile, and other ongoing collaborations such as Nutrition Sensitive Agriculture forum and more. In total, 85 stakeholders were identified, representing 8 groups of stakeholders: Non-governmental organizations - NGOs (28); Research Institutions (18); International Institutions/Donor Institutions (10); Government institutions (10); Academic Institutions (6); United Nations Organizations (6); Private sector - Buyers/ traders/aggregators (4); Civil Society Organisations (3). In addition, 8 active stakeholder platforms are identified, these are: Food System Multisectoral technical core team; Rural Economic Development and Food Security (RED&FS) Sector Working Group; Nutrition Sensitive Agriculture (NSA) forum; Seqota Declaration; National Information Platform for Nutrition (NiPN); Nutrition Development Partners Forum (NDPF); Disaster Risk management Agricultural task force (DRM-ATF).